Clinical impact of perirenal thickness on short‐ and long‐term outcomes of gastric cancer after curative surgery. Issue 4 (25th January 2022) - Eto, Kojiro; Yoshida, Naoya; Iwatsuki, Masaaki; Iwagami, Shiro; Nakamura, Kenichi; Morita, Keisuke; Ikeshima, Satoshi; Horino, Kei; Shimada, Shinya; Baba, Hideo
Abstract: Background: A variety of factors for short‐ and long‐term outcomes have been reported after radical resection for gastric cancer (GC). Obesity and emaciation had been reported to be a cause of poor short‐ and long‐term outcomes with gastrointestinal cancer. However, the indicators are still controversial. The purpose of this study was to evaluate the relationship between perirenal thickness (PT) and short‐ and long‐term outcomes after radical surgery for GC. Methods: We analyzed the data of 364 patients with GC who underwent radical surgery. We evaluated the distance from the anterior margin of the quadratus lumborum muscle to the dorsal margin of the left renal pole using computed tomography (CT) as an indicator of PT. The association between PT and clinicopathological factors and short‐ and long‐term outcomes was evaluated. Results: The PT data were divided into low, normal, and high groups by gender using the tertile value. We found that the PT low group was 121 patients, normal group was 121 patients, and high group was 122 patients. Multivariate analyses showed that the high PT group was an independent risk factor for a short‐outcome after curative surgery in GC patients (odds ratio 2.163; 95% confidence interval [CI] 1.156–4.046; P  = .016). And the low PT group was an independent risk factor for overall survival (hazard ratio 2.488; 95% CI 1.400–4.421; P  = .0019) and relapse‐free survival (hazard ratio 2.342; 95% CI 1.349–4.064; P  = .0025) after curative surgery in GC patients. Conclusion: Perirenal thickness is a simple and useful factor for predicting short‐ and long‐term outcomes after radical surgery for GC. Abstract : This study revealed that perirenal thickness was associated with short‐ and long‐term outcomes after curative surgery in gastric cancer. Perirenal thickness is a simple and useful factor for predicting short‐ and long‐term outcomes after curative surgery for gastric cancer.